2000
DOI: 10.1038/35037627
|View full text |Cite
|
Sign up to set email alerts
|

Quorum-sensing signals indicate that cystic fibrosis lungs are infected with bacterial biofilms

Abstract: The bacterium Pseudomonas aeruginosa permanently colonizes cystic fibrosis lungs despite aggressive antibiotic treatment. This suggests that P. aeruginosa might exist as biofilms--structured communities of bacteria encased in a self-produced polymeric matrix--in the cystic fibrosis lung. Consistent with this hypothesis, microscopy of cystic fibrosis sputum shows that P. aeruginosa are in biofilm-like structures. P. aeruginosa uses extracellular quorum-sensing signals (extracellular chemical signals that cue ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
1,016
1
11

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,377 publications
(1,065 citation statements)
references
References 14 publications
29
1,016
1
11
Order By: Relevance
“…These results provide a strong functional correlation between LPS modification enzyme levels and the LPS structural modifications seen in this environmental condition, confirming the validity of ICAT analysis. A number of P. aeruginosa virulence factors are regulated by quorum sensing bacterial communication via small molecule signals N-(3-oxododecanoyl)-L-homoserine lactone (3OC12-HSL) and N-butyryl-L-homoserine lactone (C4-HSL) [24,25,26,13]. The quantitative protein profiles indicated that magnesium limitation induced several quorum sensing proteins including the 3OC12-HSL synthase LasI [27] and the starvation and general stress-response regulator RelA [28,29] (Table 2).…”
Section: Quantitative Proteomic Analysis Defined P Aeruginosa Virulementioning
confidence: 99%
See 1 more Smart Citation
“…These results provide a strong functional correlation between LPS modification enzyme levels and the LPS structural modifications seen in this environmental condition, confirming the validity of ICAT analysis. A number of P. aeruginosa virulence factors are regulated by quorum sensing bacterial communication via small molecule signals N-(3-oxododecanoyl)-L-homoserine lactone (3OC12-HSL) and N-butyryl-L-homoserine lactone (C4-HSL) [24,25,26,13]. The quantitative protein profiles indicated that magnesium limitation induced several quorum sensing proteins including the 3OC12-HSL synthase LasI [27] and the starvation and general stress-response regulator RelA [28,29] (Table 2).…”
Section: Quantitative Proteomic Analysis Defined P Aeruginosa Virulementioning
confidence: 99%
“…The result of such envelope modification is increased bacterial resistance to antimicrobial peptides [10,11] and increased proinflammatory signaling through the human Tlr4 receptor [12]. P. aeruginosa was also isolated from CF patients' airways in the form of biofilms, antibiotic-resistant bacterial communities [13]. Some of the properties that are characteristic for clinical isolates of P. aeruginosa, such as synthesis of CF-specific LPS, can be also induced in vitro by growth of the bacteria in medium limited for magnesium.…”
mentioning
confidence: 99%
“…Moreover, T3SS in vitro detection was correlated with increased morbi-mortality and relapse in human P. aeruginosa ventilator-associated pneumonia and blood stream infections [55,56]. Previously, T2SS has been shown to be strongly involved in P. aeruginosa chronic infection [57]. In this work, the absence of functional T2SS or T3SS was not associated with significant decrease of the main inflammatory mediator expression by infected monolayered keratinocytes at an early time of infection (6 h).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in comparison to a number of other fluoroquinolones, clinafloxacin was noted to be the most active against efflux-mediated multidrug-resistant Pseudomonas aeruginosa, Stenotrophomonas maltophilia, and Burkholderia cepacia, all recognized pathogens in CF patients (14). This is particularly relevant in the treatment of CF pulmonary infections that are characterized by biofilms, or matrix-encased communities of bacterial cells (26). Efflux pumps play a significant role in biofilmspecific resistance to multiple classes of antibiotics, including fluoroquinolones, in bacteria such as B. cenocepacia (27,28).…”
Section: Commentarymentioning
confidence: 99%